Effect of Corporate Culture on the Effectiveness of Manufacturing Companies in Cross River State, Nigeria (American International Journal of Nursing Education and Practice, 2020)
This study examines the effect of corporate culture on organizational effectiveness in the selected manufacturing companies in Cross River State, Nigeria. Two manufacturing companies were selected for the study. In this study four research hypotheses were also formulated. Cross sectional survey design was used in the methodology and data was gathered using the Denison Organisational Culture Survey (DOCS) instrument. A total of 264 employees of the selected manufacturing companies were randomly drawn from the 778 employees of the two companies using Taro Yamane formula. A total of 251 copies of the questionnaire were retrieved and analyzed. Simple linear regression and Pearson Correlation Statistical tools from SPSS version 22 were used to test the hypotheses for significance and relationships. The findings indicate that involvement, consistency, adaptability and sense of mission positively influenced organisational effectiveness. There are significant relationships between the four dimensions of corporate culture. Based on these findings we concluded that corporate culture has significant influence on organizational effectiveness in the selected manufacturing companies in Cross River State, Nigeria. It is therefore recommended that managers of the selected manufacturing companies should always ensure the alignment of culture with business strategy, should build culture as an explicit role with set objectives, should let employees share in the organisation’s mission and decision making processes and should develop new templates to manage adaptability since adaptive culture that is consistent and responsive to individual involvement that encourages shared mission will be most effective with potentials of becoming industry leader.